Physical characteristics and Chemical compositions of Leaves extracts of Sorindeia grandifolia Engl. (Anacardiaceae) harvested at Kato, Benin - NOUDOGBESSI, JEAN PIERRE AKODOGBO; ALITONOU, GUY ALAIN; AVLESSI, FÉLICIEN; FIGUEREDO, GILLES; Chalard, Pierre; CHALCHAT, Jean C.; SOHOUNHLOUE, KOKO CODJO DOMINIQUE (My University, 2013)
The results brought back at the end of this work concern various chemical constituents of S. grandifolia leaves collected in Benin. The major compounds ( 4%) of essential oils obtained after hydrodistillation and analysis by coupling gas chromatography with spectrometry mass are constituted of : limonene (20.2%), (E)--ocimene (7.6-17.8%), (Z)--ocimene (11.4%), -cadinene (7.0%), selin-11-en-4--ol (4.5-5.7% ), palmitic acid (4.3-6.2%), -pinene (5.5%), α-selinene (5.5%), -phellandrene (5.2%), β-selinene (4.9%), β-elemene (4.5%).The lipidic fractions realized from petroleum ether extracts are marked by importants rates of arachidic acid (22.5%), palmitic acid (20.3%) and of linoleic acid (15.9 %). The phytochemical analysis showed relatively a large content of coumarins, gallic tannins, flavones, leucoanthocyans and saponins in opposition to the other secondary metabolites.
Keywords: limonene; arachidic acid; metabolites; coumarins